Exploring Figurative Language in a “How Make Millions Before Grandma Dies” Film - Sinaga, Eunike Angita; Manik, Sondang; Pasaribu, Arsen Nahum (Lembaga Riset dan Inovasi Almatani, 2025)
The purpose of this study is to analyze the figurative language used in the film entitled